2013
DOI: 10.1038/hdy.2013.108
|View full text |Cite
|
Sign up to set email alerts
|

Phylogeny and vicariant speciation of the Grey Rhebok, Pelea capreolus

Abstract: A South African endemic antelope, the Grey Rhebok (Pelea capreolus), has long been an evolutionary enigma in bovid systematics-its phylogenetic intractability attributed to its curious combination of derived and primitive morphological attributes and the consequences of a rapid radiation. By using a combination of DNA sequences, chromosomal characteristics and quantitative and qualitative morphological features we show that the species is a sister taxon to a clade that comprises the waterbuck, reedbuck and all… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(6 citation statements)
references
References 39 publications
0
6
0
Order By: Relevance
“…The distinct suite of properties include: extended separation of catchment source from the sink; the deeply weathered catchment which buffers inter-annual base flow; the aridity of the surrounding areas; the porous basin-fill; when coupled with the active tectonics creating the ‘accommodation space’ for the lake and fan sediments and perhaps driving the reorganisation of the regional drainage system leading to lake drainage. They have made the basin an area of hydrological importance in the past and give the Delta today its distinctive vegetation, which supports a rich fauna of international importance 44 and which shows evidence of evolutionary vicariance in at least one antelope taxon 45 . We suggest that one of the contributing factors to this rich vegetation is the capacity of the hydrological and hydrogeological system to buffer seasonal and decadal variations in vegetation vigour.…”
Section: Resultsmentioning
confidence: 78%
“…The distinct suite of properties include: extended separation of catchment source from the sink; the deeply weathered catchment which buffers inter-annual base flow; the aridity of the surrounding areas; the porous basin-fill; when coupled with the active tectonics creating the ‘accommodation space’ for the lake and fan sediments and perhaps driving the reorganisation of the regional drainage system leading to lake drainage. They have made the basin an area of hydrological importance in the past and give the Delta today its distinctive vegetation, which supports a rich fauna of international importance 44 and which shows evidence of evolutionary vicariance in at least one antelope taxon 45 . We suggest that one of the contributing factors to this rich vegetation is the capacity of the hydrological and hydrogeological system to buffer seasonal and decadal variations in vegetation vigour.…”
Section: Resultsmentioning
confidence: 78%
“…1; derived from use of high-throughput phylogenomics); (5) Robinson et al (2014:fig. 3b; based on mt DNA and nuclear gene fragments and chromosomal characters); and (6) Robinson et al (2014: fig. 3c; based on the genomic data in the previous result together with morphological characters).…”
Section: Discussionmentioning
confidence: 99%
“…The quoted support affirms that the above are good working hypotheses. More problematic is how the waterbuck lineage, subgenus Kobus A. Smith, 1840, relates to Hydrotragus and Adenota in extant Kobus: although a waterbuck-Adenota sister group is favored by the majority (5, 3, 1, 1), in two of the three supporting results, (5) and (6) from Robinson et al (2014), the support is weak. Study (3) found a waterbuck-Hydrotragus sister group (also found by Vrba et al, 1994, based on skull characters).…”
Section: Discussionmentioning
confidence: 99%
“…Thus no species remain unrecognized; for surely, give or take adjustments of the 'subspecies' status of a few populations, is it not true that species lists were completed decades back? Moreover, where their conservation profile is disregarded as just population segments, subspecies Robinson et al, 2014). are of negligible evolutionary importance (Corbet, 1997). We argue that all 'de facto' factors such as these have motivated zoos and wildlife authorities to mix supposedly 'conspecific' stocks both in situ and ex situ (but see Dathe, 1978).…”
Section: (3) Why 'Taxonomic Inflation' Is a Misnomermentioning
confidence: 99%